If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m-2m=m(2-2m)
We move all terms to the left:
m-2m-(m(2-2m))=0
We add all the numbers together, and all the variables
m-2m-(m(-2m+2))=0
We add all the numbers together, and all the variables
-1m-(m(-2m+2))=0
We calculate terms in parentheses: -(m(-2m+2)), so:We get rid of parentheses
m(-2m+2)
We multiply parentheses
-2m^2+2m
Back to the equation:
-(-2m^2+2m)
2m^2-2m-1m=0
We add all the numbers together, and all the variables
2m^2-3m=0
a = 2; b = -3; c = 0;
Δ = b2-4ac
Δ = -32-4·2·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{9}=3$$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3}{2*2}=\frac{0}{4} =0 $$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3}{2*2}=\frac{6}{4} =1+1/2 $
| 59.29=2*3.14*r | | 2x=242/5 | | 4x9x2=36X2= | | 3p-3(3-2p)=4(p-2)-11 | | 5x+10=4+x | | 8/3.5=12/x | | x^2-100x+225=0 | | 5m+4=3-4(m+ | | -8(x+2)+3x+5=6x+10 | | 4n+n=16+4 | | (3x-5)(10-0.6x-2)+(x-5)(20-x)=259000 | | 3x+17=2x+7 | | x-(-99)=1 | | (3x-5)(10-0.6x-2)+(x-5)(20-x)=259,000 | | 12+5x=2x+3 | | x-(99)=1 | | x-104=-75 | | 7x+5x-3=27 | | -3m-6=2 | | 2x+7=68 | | 68+2x=7 | | 2=32+5x | | 5(v+3)+(v-2)=2(v+4)-2(v-3) | | 54+2x=68 | | (4x+7)^2=-7(7+4x) | | (4x-7)^2=-7(7-4x) | | 4a/8=4 | | 18=f-2 | | (4x-7)^2=2(7-4x) | | 9-7x=-21 | | .60(x+38000)=51000 | | 6x+42=252 |